2008
DOI: 10.1016/j.biocon.2008.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Status, distribution and long-term changes in the waterbird community wintering in Doñana, south–west Spain

Abstract: PUBLICATION,[VOL#, ISSUE#, species whose populations at Doñana exceed 1% of the biogeographical flyway population. For at least one month of the year, mean counts were around 10% of the flyway population for six species. The natural, temporary marshes of Doñana National Park were particularly important for Anatidae, ricefields for gulls, white storks and grey herons, fish ponds for flamingos, cormorants and avocets, and salt pans for shelduck.Four Anatidae species have undergone long-term declines and eight no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
206
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(216 citation statements)
references
References 33 publications
6
206
0
4
Order By: Relevance
“…The permanently inundated lagoons at Veta la Palma provide a vital refuge for these ducks and other waterbirds during the dry season and until winter rains re-flood the Doñana marshes bird populations in Veta la Palma can reach 300,000 (Kloskowski et al 2009). These lagoons are particularly important feeding grounds for great cormorants (Phalacrocorax carbo), greater flamingos (Phoenicopterus roseus), black winged stilts (Himantopus himantopus) and pied avocets (Recurvirostra avosetta) (Rendon et al 2008), and feeding by flamingos, coots and ducks has been shown to have a significant influence on the biomass of both macrophytes and invertebrate populations Rodriguez-Perez and Green 2012). In parallel with the habitat and food support to birds, a total of more than 800 t of semi-extensive and extensively produced fish and shrimp are harvested annually .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The permanently inundated lagoons at Veta la Palma provide a vital refuge for these ducks and other waterbirds during the dry season and until winter rains re-flood the Doñana marshes bird populations in Veta la Palma can reach 300,000 (Kloskowski et al 2009). These lagoons are particularly important feeding grounds for great cormorants (Phalacrocorax carbo), greater flamingos (Phoenicopterus roseus), black winged stilts (Himantopus himantopus) and pied avocets (Recurvirostra avosetta) (Rendon et al 2008), and feeding by flamingos, coots and ducks has been shown to have a significant influence on the biomass of both macrophytes and invertebrate populations Rodriguez-Perez and Green 2012). In parallel with the habitat and food support to birds, a total of more than 800 t of semi-extensive and extensively produced fish and shrimp are harvested annually .…”
Section: Methodsmentioning
confidence: 99%
“…The Natural Park is a Ramsar wetland of international importance being a significant transitory area for the six million migratory birds that pass through on the European -West African flyway and a major overwintering site for more than 500,000 waterbirds (UNEP 2011). It is also the most important European wintering site for ducks (Anatidae) (Rendon et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, irrigation ponds should be included in the official waterbird censuses, which are conducted every year in order to obtain more precise knowledge of the real population in the study area (Martí anddel Moral 2003, 2004). Moreover, the importance of ponds, like other artificial wetlands (Maeda 2001;Tourenq et al 2001;Múrias et al 2002;McKinstry and Anderson 2002;Elphick and Oring 2003;Paracuellos and Telleria 2004;Ma et al 2004;Santoul et al 2004;Okes et al 2008, Rendon et al 2008, increases as a result of the degradation of natural ones. In our case, the value of ponds for waterbirds conservation is higher in the breeding season, as a consequence of the characteristics of the climate in the zone.…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…Many authors have already studied the relative importance of artificial wetlands, and most have found that they can provide suitable habitats for waterbirds (Tourenq et al 2001;McKinstry and Anderson 2002;Paracuellos and Telleria 2004;Santoul et al 2004;Okes et al 2008, Rendon et al 2008. Salt marshes, aquaculture fish ponds, mine impoundments, gravel pits, rice fields or irrigation ponds are able to provide alternative or substitute habitats for waterbirds communities as well as for amphibians (Knutson et al 2004;Julian et al 2006) plants or invertebrates (Nicolet et al 2004;Taft and Haig 2005;Abellán et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The aquatic bird fauna is in fact extremely important in terms of ecological relevance and conservation in all the lagoons of the Mediterranean region and several aspects of their ecology make them useful for understanding the wetland dynamics (Josens et al, 2012). Birds associated with aquatic habitats have been shown to track changes in such natural (water level and lake productivity) or anthropogenic environmental factors, both on short (months) and long (years) temporal scales and at both the species and community levels (almaraz, amat, 2004;rendón et al, 2008;Josens et al, 2012). Long-term studies of animal populations have been often considered of paramount importance in understanding the frequency, duration and amplitude of variations in the ecological systems.…”
Section: Introductionmentioning
confidence: 99%